Evaluation of Flower Dynamics, Fruit Yield and Quality of Pomegranate under Different Semi-arid Location of West Bengal - Sannigrahi, Sudipta; Datta, Soustav; Mondal, Tanmoy; Dey, Susmita; Sarkar, Sushanta Kumar (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during January to June of 2018–19 to 2020–21 at the four locations (Chhatna, Pathri, Bamunpathri and Damodarpur) of red and lateritic agro-climatic zone of West Bengal, India to study the flowering dynamics and reproductive system of pomegranate cv. Bhagwa. The experiment was laid out in a Randomized Block Design (RBD). The observations regarding flowering and fruiting of pomegranate, based on pooled data of experimental period exhibited significant variation in different locations. These variations included duration of flowering (144.20–48.45 days), number of flower buds (148.15–47.45), number of flowers (130.60–38.3) in which anthesis observed, number of flowers dropped (93.00–6.85) before anthesis, number of flowers formed on young shoot (9.15–1.15) and aged shoot (26.55-12.30), number of hermaphrodite flowers (37.50–6.15), fruit drop per tree-1 (46.65–24.94 %), number of fruits per tree at harvest (33.90-4.35), weight of fruit (198.06–85.17 g), fruit yield (6.70–0.36 kg tree-1), fresh weight of seeds (31.22–16.42 g), aril rind ratio (3.44–1.58), seed test weight (6.54–4.0 g), TSS (14.45–13.24 °B), acidity (0.75–0.17%), total sugar (14.17–13.53%), reducing sugar (10.96–10.62%) and non-reducing sugar (3.21–2.78 %) at harvest. Most of the fruit yield and fruit quality parameters were observed highest at the Damodarpur location. It may be due to good vigour of plants, normal crop load, climatological factors and soil conditions. It can be concluded that the Damodarpur location could be the best location for improved production and productivity of pomegranate and the possibility of obtaining high quality fruits.